2018
DOI: 10.1104/pp.17.01579
|View full text |Cite
|
Sign up to set email alerts
|

The Polycomb-Group Repressor MEDEA Attenuates Pathogen Defense

Abstract: Plants recruit positive and negative regulators for fine tuning the balance between growth and development. Negative regulators of pathogen defense generally modulate defense hormone biosynthesis and signaling. Here, we report a mechanism for attenuation of the defense response in Arabidopsis (), which is mediated by the polycomb-group repressor MEDEA (MEA). Our results showed that pathogen inoculation or exogenous application of salicylic acid, methyl jasmonate, or the bacterial 22-amino acid domain of flagel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 75 publications
0
27
0
Order By: Relevance
“…As previously discussed, the MEA H3K27me3 histone acetyltransferase has been shown to be an immune repressor, and its mutation reported to render Arabidopsis highly resistant to both a necro‐ and a hemibiotrophic pathogen (Roy et al ., ). Interestingly, the mea‐6 mutant displays normal SA content compared with the WT under control conditions, while its induction is significantly higher when challenged with Pst DC3000.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As previously discussed, the MEA H3K27me3 histone acetyltransferase has been shown to be an immune repressor, and its mutation reported to render Arabidopsis highly resistant to both a necro‐ and a hemibiotrophic pathogen (Roy et al ., ). Interestingly, the mea‐6 mutant displays normal SA content compared with the WT under control conditions, while its induction is significantly higher when challenged with Pst DC3000.…”
Section: Discussionmentioning
confidence: 97%
“…Flowering is another biological process widely recognized for being controlled by PcG proteins, mainly by components of the PRC1 and VRN−PCR2 complex in which LHP1 (LIKE HETEROCHROMATIN PROTEIN 1) and CLF (CURLY LEAF) are major players, respectively (Wang et al ., ). A recent study showed that the formerly thought embryo‐specific H3K27me3 methyltransferase MEA (MEDEA) is induced by biotic stress and involved in the repression of immune responses in Arabidopsis through the targeting of defense genes, thus indicating that PRCs activity is not limited, at least in plants, to the regulation of developmental transitions but that they can also contribute to stress responses (Roy et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The expression of MEA could be induced by either pathogen inoculation or exogenous application of JA or SA. Indeed, MEA can suppress both PTI and ETI in Arabidopsis [156,183]. Specifically, MEA is able to interact with LONG-CHAIN BASE KINASE1 (LCBK1) and impair its function, which in turn results in a loss of pathogen-induced stomatal closure and PTI; meanwhile, MEA could be recruited by DROUGHT-INDUCED 19 (Di19) to implement H3K27me3 modification on the immune receptor RESISTANCE TO P. SYRINGAE2 (RPS2) loci, thereby repressing its expression and attenuating AvrRpt2 effector-mediated ETI [156,183].…”
Section: Biotic Stressmentioning
confidence: 99%
“…Specifically, MEA is able to interact with LONG-CHAIN BASE KINASE1 (LCBK1) and impair its function, which in turn results in a loss of pathogen-induced stomatal closure and PTI; meanwhile, MEA could be recruited by DROUGHT-INDUCED 19 (Di19) to implement H3K27me3 modification on the immune receptor RESISTANCE TO P. SYRINGAE2 (RPS2) loci, thereby repressing its expression and attenuating AvrRpt2 effector-mediated ETI [156,183]. Consistently, MEA-overexpressing transgenic plants are susceptible to fungal pathogens, bacterial pathogens, and Pst-AvrRpt2, whereas mea-6 mutant plants are more resistant to bacterial pathogens [156,183]. Moreover, loss of SWN caused a significantly increased hypersensitive response (HR) during the time course of AvrRpt2 induction, revealing a role of SWN in attenuating PCD [224].…”
Section: Biotic Stressmentioning
confidence: 99%
“…In Arabidopsis, the first reported Di19 protein was Di19-1, which participated in response to drought stress by binding to the TACA(A/G)T elements in the pathogenesis-related PR1 , PR2 , and PR5 promoters and positively regulating their expressions [19,20]. Recently, Di19-1 was also found to interact with polycomb-group repressor MEDEA (MEA) and recruit it at the RESISTANCE TO P. SYRINGAE 2 ( RPS2 ) promoter to negatively regulate the immune response [21]. Di19-3, as a transcriptional activator, was involved in plant response to high salinity, drought, ABA, and H 2 O 2 [22].…”
Section: Introductionmentioning
confidence: 99%